2016
DOI: 10.1111/bjh.13993
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib in the treatment of refractory thrombotic thrombocytopenic purpura

Abstract: Acquired thrombotic thrombocytopenic purpura (TTP) is a rare, life-threatening condition caused by autoantibody-mediated inhibition of ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type-1 motif, 13). Therapeutic plasma exchange (TPE) improves survival, but disease may be refractory despite therapy. Management and treatment response of refractory TTP is variable, with rituximab and other immunosuppression often being used. Case reports have suggested a benefit of the proteasome inhibitor, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 36 publications
2
52
0
4
Order By: Relevance
“…Although absolute numbers are low, the apparent high response rate in TTP is consistent with a recent series of 6 consecutive cases from UK referral centers where 5 patients achieved remission. 16 Although formal prospective evaluation of proteasome inhibition in ultra-rare diseases like TTP is unlikely to be feasible, more common presentations such as refractory AIHA should be amenable to trial development. Registry data may also prove invaluable for capturing disease-specific response rates and safety end points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although absolute numbers are low, the apparent high response rate in TTP is consistent with a recent series of 6 consecutive cases from UK referral centers where 5 patients achieved remission. 16 Although formal prospective evaluation of proteasome inhibition in ultra-rare diseases like TTP is unlikely to be feasible, more common presentations such as refractory AIHA should be amenable to trial development. Registry data may also prove invaluable for capturing disease-specific response rates and safety end points.…”
Section: Resultsmentioning
confidence: 99%
“…7 On this basis, bortezomib has been prospectively evaluated as an adjunct to rituximab and plasma exchange (PEX) as a means to deplete alloantibodies in solid organ transplant recipients. 8 Moreover, reports of activity in autoimmune diseases including AIHA, 9,10 immune thrombocytopenia, 11 and TTP [12][13][14][15][16] are emerging. Following our initial success utilizing bortezomib in a patient with refractory TTP, 12 we now report our cumulative experience using this treatment approach in a series of patients with refractory antibody-mediated autoimmune hematological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, they could not demonstrate if the response was secondary to rituximab or bortezomib [7]. Similarly, Patriquin et al reported a series of six refractory TTP patients all of whom received PEX, methylprednisolone, and rituximab besides bortezomib [11]. Bortezomib was given very early in the disease process (range 6–22 days) which is understandable given the often aggressive nature of TTP and hence the resultant desperate therapy alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, NAC as a single therapy, was unable to reverse TTP signs nor dissolve preexisting VWF‐rich thrombi 32. Case reports have shown successful use of NAC in patients with refractory TTP as evidenced by normalization of platelet function and ADAMTS13 activity in four patients33, 34 but was unsuccessful in three others 35, 36, 37. A pilot study to evaluate the use of NAC in suspected TTP is underway (NCT01808521).…”
Section: N‐acetylcysteinementioning
confidence: 99%
“…Its mechanism of action in TTP is thought to be due to the elimination of plasma cells that produce the autoantibodies against ADAMTS13. The evidence for the use of this drug is still limited to case reports35, 40, 41, 42, 43, 44, 45 and a case series37 that reported 14 cases of TTP that were refractory to PEX, steroids, and rituximab. All but one patient recovered from their acute episode of TTP.…”
Section: Bortezomibmentioning
confidence: 99%